Performance de gênero no feminino e no plural: travestilidade, violência e abjeção - Santos, Gabriela de Morais (2016)
This research investigates on gender performance in trans women, through bibliographical research, with the aim of building the script: family home scenic. We analyze essential concepts of gender studies to discuss the experience of these subjects, a brief history of motion picture LGBTT, data on violence suffered by this group, in official reports and hemerográficos, noting the fragility of the data and the high degree of imprecision. Also we discuss about the feminine, a gender role that socially generates vulnerabilities, as can be seen in cisgêneras women, Transgender and gay men effeminate. The bibliographical research served the theatrical script homestay, churning out a product accessible to the community.